STIM1-dependent Store-Operated Ca(2+) Entry is Required for Pathological Cardiac Hypertrophy - Luo, Xiang (2011)
BACKGROUND: Alterations in intracellular Ca(2+) homeostasis are an important trigger of pathological cardiac remodeling; however, mechanisms governing context-dependent changes in Ca(2+) influx are poorly understood. Store-operated Ca(2+) entry (SOCE) is a major mechanism regulating Ca(2+) trafficking in numerous cell types, yet its prevalence in adult heart and possible role in physiology and disease are each unknown. The Ca(2+)-binding protein, stromal interaction molecule 1 (STIM1), is a Ca(2+) sensor in the sarcoplasmic reticulum (SR), capable of triggering SOCE by interacting with plasma membrane Ca(2+) channels. METHODS AND RESULTS: We report that SOCE is abundant and robust in neonatal cardiomyocytes; however, SOCE is absent from adult cardiomyocytes. Levels of STIM1 transcript and protein correlate with the amplitude of SOCE, and manipulation of STIM1 protein levels (via shRNA) or activity (via expression of constitutively active or dominant-negative mutants) reveal a critical role for STIM1 in activating SOCE in cardiac myocytes. In neonatal hearts a recently identified STIM1 splice variant (STIM1L) is predominant but diminishes with maturation, only to reemerge with agonist- or afterload-induced cardiac stress. To test for pathophysiological relevance, we evaluated both in vitro and in vivo models of cardiac hypertrophy, finding that STIM1 expression is re-activated by pathological stress to trigger significant SOCE-dependent Ca(2+) influx. STIM1 amplifies agonist-induced hypertrophy via activation of the calcineurin-NFAT pathway. Importantly, inhibition of STIM1 suppresses agonist-triggered hypertrophy, pointing to a requirement for SOCE in this remodeling response. CONCLUSIONS: Stress-triggered STIM1 re-expression, and consequent SOCE activation, are critical elements in the upstream, Ca(2+)-dependent control of pathological cardiac hypertrophy.